INTEGRATING PROBLEM-BASED LEARNING INTO CREDIT-MODULE SYSTEMS TO ENHANCE INDEPENDENT LEARNING COMPETENCIES: EVIDENCE FROM ENGLISH LANGUAGE AND LITERATURE PROGRAMMES IN UZBEKISTAN (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
The integration of Problem-Based Learning (PBL) within credit-module educational frameworks has attracted considerable scholarly attention as higher education institutions across Central Asia undergo systemic reform [1.12]. This study investigates the effects of PBL implementation on independent learning competencies among undergraduate students enrolled in English Language and Literature programmes at three higher education institutions in Uzbekistan. Employing a mixed-methods design, the study involved 184 participants across two academic years (2022–2024). Quantitative data were collected through validated autonomy and self-regulation scales, while qualitative data were gathered through semi-structured interviews and reflective portfolios. Findings indicate that PBL-integrated credit-module courses significantly improved students’ metacognitive awareness, self-directed task engagement, and critical thinking in English language learning contexts [8.236]. Statistical analysis revealed a mean pre-post gain of 18.3 points on the Learner Autonomy Index (p < 0.001). The study discusses these outcomes in relation to Uzbekistan’s ongoing higher education reforms and situates findings within global PBL literature. Practical recommendations for curriculum designers and faculty developers in EFL/ELL contexts are provided.